Peran Guru Kelas Dalam Penguatan Konsentrasi Belajar Sebagai Bentuk Pelaksanaan Bimbingan Konseling Siswa Kelas Rendah SD Muhammadiyah 5 Surakarta - Kusumaningrum, Hartanti, Dra. Risminawati, M.Pd (2017)
The role of the classroom teacher is indispensable in substantiating the concentration of learning on students, because the task of teachers not only teach and convey the materials alone but also as supervising students in overcoming learning problems. 1) To describe the role of classroom teachers in strengthening the concentration of students' low grade SD Muhammadiyah 5 Surakarta, 2) forms of implementation of counseling students low grade SD Muhammadiyah 5 Surakarta, 3) the role of classroom teachers in the strengthening of the concentrations studied as a form of implementation of the guidance and counseling of students low grade SD Muhammadiyah 5 Surakarta, 4) barriers and solutions to strengthen the role of classroom teachers in the concentrations studied as a form of implementation of the guidance counseling low-grade students of SD Muhammadiyah Surakarta 5. This type of research is qualitative research This research data analysis using interactive analysis model Miles & Huberman. Data collection techniques used are interviews, observation, and documentation. The validity of this research data using triangulation techniques and sources. (1) In giving concentration on students learning reinforcement teacher classes do change seats, giving the intermezzo/entertainment, using media learning, delivery of reward, giving praise and applause.(2) Implementation guidance counseling was carried out by each classroom teacher, yet there are special teachers in the field of counseling, guidance conducted individual and group counseling services are integrated with learning.(3) Classroom teacher are always preparing students begin studying the use of media and learning methods using ice breaking on the sidelines of learning.(4) Resistance gets less students motivation in learning, environmental factors are less support, lack of awareness of the students will be learning readiness. The solution is always gives master class on student motivation, prepare the classrooms are comfortable and conducive.